Technological innovations in mental healthcare: harnessing the digital revolution - Hollis, Chris; Morriss, Richard; Martin, Jennifer; Amani, Sarah; Cotton, Rebecca; Denis, Mike; Lewis, Shôn (Royal College of Psychiatrists, 2015)
Digital technology has the potential to transform mental healthcare by connecting patients, services and health data in new ways. Digital online and mobile applications can offer patients greater access to information and services and enhance clinical management and early intervention through access to real-time patient data. However, substantial gaps exist in the evidence base underlying these technologies. Greater patient and clinician involvement is needed to evaluate digital technologies and ensure they target unmet needs, maintain public trust and improve clinical outcomes.